Rancangan Pengering Ikan Teri Berteknologi Hybrid Untuk Daerah Pesisir Berbasis Arduino - ismail simatupang; Dina Maizana (Universitas Medan Area, 2025)
Drying anchovies is an important step in the processing of fishery products, especially in coastal areas such as Medan Labuhan District. This study aims to design and build a hybrid anchovy dryer that utilizes renewable energy and Arduino-based control. This drying system integrates heat sources from sunlight and electric heaters to increase the efficiency of the drying process, especially in uncertain weather conditions. Testing methods are used to evaluate the performance of the tool, focusing on drying time and the quality of the anchovies produced. The results of the study showed that this hybrid dryer was able to accelerate the drying process and maintain the quality of anchovies, so it is expected to increase the income of local fishermen. Thus, this innovation not only contributes to the fisheries sector, but also supports environmental sustainability through the use of renewable energy sources.